Non-Contact Radio Frequency Level Sensor Based on Wheeler Cap - Pratoomma, Prakorn; Zandamela, Abel; Narbudowicz, Adam; Chalermwisutkul, Suramate (My University, 2023)
In this paper, we propose a novel non-contact liquid level sensor based on the Wheeler cap. The sensor utilizes an electrically small antenna operating at 276 MHz enclosed within a metal cap, in conjunction with the liquid container. By analyzing the reflection coefficient at the antenna feed and evaluating the magnitude and frequency of the minimum value, the sensor enables determination of the water level. The experimental results demonstrate the sensor's effectiveness in measuring water levels within the range of 0 to 94 mm, in a water container measuring 109x109x123 mm³. Notably, minimal variations in frequency and magnitude of the minimum reflection coefficient are observed at water levels below 50 mm, while the sensor exhibits improved sensitivity for water levels above 50 mm. The proposed sensor can offer a promising level sensing solution for liquids with extreme temperatures.
2023 IEEE INTERNATIONAL SYMPOSIUM ON ANTENNAS AND PROPAGATION
Keywords: Wheeler Cap; Electrically Small Antennas; Level Sensor; Folded Spherical Helix Antenna; Internet of Things; Telecommunications; SENSORS; SMALL ANTENNAS